2014
DOI: 10.1128/jcm.01704-14
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Relatedness versus Biological Compatibility between Aspergillus fumigatus and Related Species

Abstract: e Aspergillus section Fumigati contains 12 clinically relevant species. Among these Aspergillus species, A. fumigatus is the most frequent agent of invasive aspergillosis, followed by A. lentulus and A. viridinutans. Genealogical concordance and mating experiments were performed to examine the relationship between phylogenetic distance and mating success in these three heterothallic species. Analyses of 19 isolates from section Fumigati revealed the presence of three previously unrecognized species within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
1
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(75 citation statements)
references
References 47 publications
2
70
1
2
Order By: Relevance
“…Subsequent polyphasic taxonomic re‐examination of one of the isolates from that case (isolate CM 5623) suggested that it belonged to a novel species designated as A. felis , which also causes invasive aspergillosis in dogs and cats (Barrs et al ., ). Finally, a recently refined phylogeny placed isolate CM 5623 into a separate clade and justified the proposal of yet another new cryptic representative (designated as Aspergillus parafelis ) within the broadly circumscribed species A. viridinutans (Sugui et al ., ). Notably, A. parafelis and the closely related species, Aspergillus pseudofelis and Aspergillus pseudoviridinutans , which were also proposed as novel taxa in the same study, displayed reduced susceptibility to amphotericin B, itraconazole and voriconazole, and increased virulence in different animal models with respect to the type strain of A. viridinutans (Sugui et al ., ).…”
Section: Sexual Cycle and Cryptic Species: Implications For Virulencementioning
confidence: 97%
See 3 more Smart Citations
“…Subsequent polyphasic taxonomic re‐examination of one of the isolates from that case (isolate CM 5623) suggested that it belonged to a novel species designated as A. felis , which also causes invasive aspergillosis in dogs and cats (Barrs et al ., ). Finally, a recently refined phylogeny placed isolate CM 5623 into a separate clade and justified the proposal of yet another new cryptic representative (designated as Aspergillus parafelis ) within the broadly circumscribed species A. viridinutans (Sugui et al ., ). Notably, A. parafelis and the closely related species, Aspergillus pseudofelis and Aspergillus pseudoviridinutans , which were also proposed as novel taxa in the same study, displayed reduced susceptibility to amphotericin B, itraconazole and voriconazole, and increased virulence in different animal models with respect to the type strain of A. viridinutans (Sugui et al ., ).…”
Section: Sexual Cycle and Cryptic Species: Implications For Virulencementioning
confidence: 97%
“…Finally, a recently refined phylogeny placed isolate CM 5623 into a separate clade and justified the proposal of yet another new cryptic representative (designated as Aspergillus parafelis ) within the broadly circumscribed species A. viridinutans (Sugui et al ., ). Notably, A. parafelis and the closely related species, Aspergillus pseudofelis and Aspergillus pseudoviridinutans , which were also proposed as novel taxa in the same study, displayed reduced susceptibility to amphotericin B, itraconazole and voriconazole, and increased virulence in different animal models with respect to the type strain of A. viridinutans (Sugui et al ., ). Two implications/consequences of this are: (i) the taxonomy of the genus Aspergillus is far from being settled; and (ii) clinicians require some basic knowledge on fungal taxonomy and the cryptic species concept, as these can have consequences for disease management.…”
Section: Sexual Cycle and Cryptic Species: Implications For Virulencementioning
confidence: 97%
See 2 more Smart Citations
“…Although usually distinguishable from other Aspergillus species, such as A terreus, A niger, and A flavus, based on morphologic and phenotypic characteristics, A fumigatus is a member of the section Fumigati, which consists of at least 51 phylogentically distinct species. 157 Discrimination between members of this section is difficult due to the morphologic instability but important because several species within this section are refractory to antifungal therapy. [158][159][160] Species identification cannot always be made, however, because isolates are not always recovered from patients with invasive disease.…”
Section: Trends In Antifungal Resistance Echinocandin Resistance In Cmentioning
confidence: 99%